Effect of Clinical Leadership and Teamwork on Nurse Competency in HAIs Implementation - Fitri Lismaini; Ellya Niken Prastiwi; Rokiah Kusumapradja (International Forum of Researchers and Lecturers, 2026)
Healthcare-Associated Infections (HAIs) remain a critical challenge in hospital patient safety. In Indonesia, HAIs prevalence reaches approximately 15.74%, significantly exceeding the global average of 8–9%. At Ciputra Hospital CitraRaya Tangerang, HAIs incidence reached 1.2% in 2024 and already approached 1% within the first three months of 2025. A preliminary survey of 10 nurses revealed deficiencies across all competency dimensions, including knowledge gaps (80%), skill deficiencies in hand hygiene and patient isolation (75%), lack of commitment in infection prevention (70%), communication and education issues (75%), risk management deficiencies (85%), and low participation in IPC programs (85%). This study aims to analyze the influence of clinical leadership and teamwork on nurse competency in HAIs implementation, with patient safety culture as an intervening variable. A quantitative cross-sectional design was employed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) with 122 nurses as respondents. Results demonstrated that clinical leadership, teamwork, and patient safety culture simultaneously influence nurse competency in HAIs implementation (R² = 0.52, p = 0.000). Clinical leadership has a significant positive direct effect on nurse competency (path coefficient = 0.341, p = 0.000), while teamwork showed no significant direct effect (p = 0.137). Patient safety culture emerged as the strongest predictor (path coefficient = 0.526, p = 0.000). Both clinical leadership and teamwork significantly influenced patient safety culture (0.394 and 0.321 respectively), and patient safety culture significantly mediated both relationships toward nurse competency. Strengthening clinical leadership and fostering a strong patient safety culture are the most essential strategies for improving nurse competency in HAIs prevention.